43 Comparing the assessment of end of life care in the structured judgement review with an end of life audit. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Robbins, Sara; Tredgett, Kate
Abstract : Background: The Structured Judgement Review (SJR) is a validated and standardised method for reviewing case notes of patients who died in hospital. One section assesses end of life care (EOLC); this can be rated from very poor to excellent. This audit aims to evaluate whether the SJR is providing us with an accurate assessment of the quality of EOLC in an Oncology inpatient department. Methods: This is a retrospective audit of adult patients that died on Oncology wards in 2017 and had an SJR completed. The end of life audit assessed whether the Hospital Trust's Key Performance Indicators (KPIs) were achieved. National standards were used to audit specific aspects of the individualised care plan. The care ratings and comments from each SJR were then compared with the end of life audit. Results: The notes of six patients were reviewed. The SJR ratings for EOLC were 'very good' in five cases and 'excellent' in one. However, the EOLC audit using Trust KPI's showed more variation in the quality of care. In three cases where the SJR rated 'very good' or 'excellent', this compared well with the EOLC audit where they achieved 80%–90% of Trust KPI's. In two cases where the SJR rated 'very good', they only achieved 30% of Trust KPI's. The final case was again rated 'very good', but only achieved 50% of Trust KPI's. The comments in the SJR did not discuss the same issues that the EOL audit raised. For example, some focused on treatment escalation plans being completed rather than the quality of care. Conclusion: The recorded quality of EOLC according to SJR's did not consistently reflect the quality of care being given. In order to improve the accuracy of the SJR, we attached key KPI's on EOLC to the SJR form as a prompt for reviewers.